2016
DOI: 10.1016/j.stem.2016.04.017
|View full text |Cite|
|
Sign up to set email alerts
|

Zika Virus Disrupts Neural Progenitor Development and Leads to Microcephaly in Mice

Abstract: The link between Zika virus (ZIKV) infection and microcephaly has raised urgent global alarm. The historical African ZIKV MR766 was recently shown to infect cultured human neural precursor cells (NPCs), but unlike the contemporary ZIKV strains, it is not believed to cause microcephaly. Here we investigated whether the Asian ZIKV strain SZ01 could infect NPCs in vivo and affect brain development. We found that SZ01 replicates efficiently in embryonic mouse brain by directly targeting different neuronal linages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
405
1
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(471 citation statements)
references
References 18 publications
33
405
1
6
Order By: Relevance
“…Recently, a few studies [79,80,[82][83][84][85] have evidenced the pathogenic potential of Brazilian strain of ZIKV during the development of fetus in animal models. These studies concluded that ZIKV first infects the placenta and then the brain of fetus, where it preferentially infects neural progenitor cells and decreases their viability and growth as neurospheres through down-regulation of genes that are involved in cell and organ development, and up-regulation of genes that are involved in immune responses.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a few studies [79,80,[82][83][84][85] have evidenced the pathogenic potential of Brazilian strain of ZIKV during the development of fetus in animal models. These studies concluded that ZIKV first infects the placenta and then the brain of fetus, where it preferentially infects neural progenitor cells and decreases their viability and growth as neurospheres through down-regulation of genes that are involved in cell and organ development, and up-regulation of genes that are involved in immune responses.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
“…This results in inhibited cellular proliferation and differentiation, neuronal apoptosis, thinning of the cortex and macroscopic features similar to microcephaly. Based on the results of the above stated studies [79,80,[82][83][84][85], a causal link between ZIKV infection and microcephaly could be hypothesized.…”
Section: Pathogenesis Of Microcephalymentioning
confidence: 99%
“…Both the Brazilian ZIKV strain and the Asian ZIKV strain cause abnormal cortical development in mice (Cugola et al, 2016; Li et al, 2016) that would be consistent with multiple different types of cortical malformations in human infants exposed in utero to ZIKV among both those with congenital microcephaly and those with normal head circumferences at birth. Therefore, it was not surprising when several different types of brain malformations were recently reported among infants exposed in utero to ZIKV, including polymicrogyria with schizencephalic clefts, areas of thickened cortex, areas of thinning cortex, and focal cortical dysplasia, often with asymmetry and with different types of malformations and/or brain injury in the same infant, and occurring among infants with congenital microcephaly as well as among some infants with normal head circumference at birth (de Oliveria‐Szejnfeld et al, 2016).…”
Section: In Utero Zika Virus Infection Congenital Microcephaly and mentioning
confidence: 83%
“…ZIKV invades fetal neural progenitor cells and causes brain abnormalities by at least two general mechanisms: (1) direct destruction of neuronal progenitor cells and developing neurons, and (2) disruption of the differentiation, development, and migration of neurons in the developing brain (Garcez et al, 2016; Qian et al, 2016; Sarno et al, 2016; Tang et al, 2016; Cugola et al, 2016; Li et al, 2016). Both the Brazilian ZIKV strain and the Asian ZIKV strain cause abnormal cortical development in mice (Cugola et al, 2016; Li et al, 2016) that would be consistent with multiple different types of cortical malformations in human infants exposed in utero to ZIKV among both those with congenital microcephaly and those with normal head circumferences at birth.…”
Section: In Utero Zika Virus Infection Congenital Microcephaly and mentioning
confidence: 99%
“…These are mainly observational data with minimal controls, albeit with autopsy and ultrasound data being consistent with microcephaly resulting from ZIKV infection during pregnancy 15 . ZIKV has been known to be neurotropic in animals for 60 years, with more recent murine experiments demonstrating replication in embryonic brain targeting neural progenitor cells, with consequent cell cycle arrest, apoptosis and inhibited neural progenitor cell differentiation 9,16 . This is presumed to result in the microcephalic phenotype via neuronal cell death 16 .…”
Section: Placental and Fetal Infectionmentioning
confidence: 99%